Assessing The Psychometric Properties Of A Social Communication Test For Children With Autism Spectrum Disorder In Saudi Arabia - Jaradat, Samar Abdulwahab Nafe' (2019)
The present study investigated the psychometric characteristics of the Assessment of Social Communication Skills Test (ASCST). This tool was designed to assess the social communication skills of Saudi Arabic-speaking children with Autism Spectrum Disorder (ASD) between the ages of 6:00 and 11:11 years. The research study was a scale development and validation research using a cross-sectional design. The study was conducted in the city of Jeddah in Saudi Arabia. The sample is comprised of 240 typically-developing children randomly selected from the northern region in the city of Jeddah and 36 children diagnosed with ASD selected from the rehabilitation centers. The ASCST scale is comprised of 4 subtests and include both expressive and receptive measures. The ASCST was initially evaluated by a panel of 20 validators (five psychologists, five special education teacher, five speech-language pathologists, and five parents of children with ASD). A pilot study was conducted to examine the appropriateness and validity of the initial version of the ASCST. The content validation results showed that the ASCST has a high degree of content validity. The impact of age level on the performance of the typically-developing children on the ASCST was examined using descriptive statistics and the two-way ANOVA (F). Investigation also indicated that ASCST has construct validity. For discriminant validity, the results showed differences in the performance of the participants in the six cohort groups between typically-developing children and children with ASD.